Quantitative Lesion Water Uptake as Stroke Imaging Biomarker: A Tool for Treatment Selection in the Extended Time Window?. Issue 1 (January 2022) - Broocks, Gabriel; Kemmling, Andre; Teßarek, Svenja; McDonough, Rosalie; Meyer, Lukas; Faizy, Tobias D.; Kniep, Helge; Schön, Gerhard; Nawka, Marie Teresa; Elsayed, Sarah; van Horn, Noel; Cheng, Bastian; et al.
Abstract : Background and Purpose: Patients presenting in the extended time window may benefit from mechanical thrombectomy. However, selection for mechanical thrombectomy in this patient group has only been performed using specialized image processing platforms, which are not widely available. We hypothesized that quantitative lesion water uptake calculated in acute stroke computed tomography (CT) may serve as imaging biomarker to estimate ischemic lesion progression and predict clinical outcome in patients undergoing mechanical thrombectomy in the extended time window. Methods: All patients with ischemic anterior circulation stroke presenting within 4.5 to 24 hours after symptom onset who received initial multimodal CT between August 2014 and March 2020 and underwent mechanical thrombectomy were analyzed. Quantitative lesion net water uptake was calculated from the admission CT. Prediction of clinical outcome was assessed using univariable receiver operating characteristic curve analysis and logistic regression analyses. Results: One hundred two patients met the inclusion criteria. In the multivariable logistic regression analysis, net water uptake (odds ratio, 0.78 [95% CI, 0.64–0.95], P =0.01), age (odds ratio, 0.94 [95% CI, 0.88–0.99]; P =0.02), and National Institutes of Health Stroke Scale (odds ratio, 0.88 [95% CI, 0.79–0.99], P =0.03) were significantly and independently associated with favorable outcome (modified Rankin Scale score ⩽1), adjusted for degree of recanalization and Alberta Stroke Program Early CT Score. A multivariable predictive model including the above parameters yielded the highest diagnostic ability in the classification of functional outcome, with an area under the curve of 0.88 (sensitivity 92.3%, specificity 82.9%). Conclusions: The implementation of quantitative lesion water uptake as imaging biomarker in the diagnosis of patients with ischemic stroke presenting in the extended time window might improve clinical prognosis. Future studies could test this biomarker as complementary or even alternative tool to CT perfusion. Abstract : Supplemental Digital Content is available in the text.